Safety of Drugs in Breastfeeding Women With CKD - Paula Parnizari; Michelle A. Hladunewich; Jonathan Zipursky (Kidney International Reports, 2025)
Introduction: The benefits of breastfeeding are widely recognized. Because of lack of evidence, women may forego breastfeeding or decline treatments that impact long-term renal survival. Therefore, we systematically reviewed the evidence on the breastfeeding safety of drugs commonly prescribed to women with chronic kidney disease (CKD). Methods: We conducted bibliographic search on available databases, including PUBMED, REPROTOX, and LACTMED. Results: We reviewed a total of 81 observational studies and case reports. Among renin-angiotensin system inhibitors, enalapril and captopril are safe for breastfeeding. Based on limited evidence, quinapril, benazepril, candesartan, and valsartan are likely acceptable for use during breastfeeding. We found no compelling human data regarding the safety of other renin-angiotensin system inhibitors or sodium-glucose cotransporter type 2 (SGLT2) inhibitors, finerenone, sparsentan, or glucagon-like peptide-1 receptor agonists (GLP1RAs) in lactation. Immunosuppressive agents, including azathioprine, cyclosporine, tacrolimus, budesonide, rituximab, and eculizumab are acceptable for use during breastfeeding. Belimumab is most likely safe; however, data are limited. Data on mycophenolate use are conflicting, and the general recommendation is avoidance during lactation. No studies were found on the safety of breastfeeding while on the newer complement inhibitors, including avacopan, ravulizumab, iptacopan, and pegcetacoplan. These drugs should used with caution in breastfeeding until data become available. Conclusion: Human lactation data on the safety of most drugs used in the treatment of CKD are limited, making evidence-based recommendations challenging. Emerging pharmacometrics techniques can contribute to the safety assessment of drugs in breastfeeding, overcoming ethical and practical issues associated with clinical trials in this population.